The awakening course : the secret to solving all problems - Vitale, Joe, 1953- (Hoboken, NJ : Wiley, 2011)
The author presents a program explaining the four stages of awakening. He offers a step-by-step approach for finding and achieving one's goals and desires, as well as a path to complete mind, body, and spiritual transformation.
Explains how to achieve a total mind, body, and spiritual transformation--and ultimately success--through positivity and shifting perspectives.
What to expect -- Stage one : victimhood -- Stage two : empowerment -- Stage 3 : Surrender -- Stage 4 : awakening -- The awakened millionaire -- The awakened relationship -- What do you want? -- Zero limit answers.
Includes bibliographical references (p. 215-222) and index.
Keywords: Success; Wakefulness; Transcendence (Philosophy).; Life skills; Success; Transcendentalism; Life skills